Comparison between protein functional properties of two rice cultivars - Pinciroli, María (2009)
The functional properties of proteins from a high-protein?content rice cultivar (Nutriar) were analyzed and compared with those from a usual Latin-American cultivar (El Paso 144). Isolates from brown and milled flours were prepared and their emulsifying, foaming, and hydration properties studied. The four isolates displayed a very low solubility within a wide range of moderate pH, but demonstrate a significantly higher solubility at extreme pHs (either high or low). Nutriar isolates had a significantly higher solubility and greater surface properties than El Paso 144 isolates. The Nutriar isolate from brown flour was more soluble at pH 9 than the other isolates and moreover showed the highest capacity for forming and stabilizing foams and emulsions. In contrast, the Nutriar isolate from milled rice exhibited a higher solubility and greater foaming properties at an acid pH. The surface properties and solubility were significantly correlated among the four samples. All four isolates exhibited good water imbibition and water-holding capacities.